(untitled) (Journal of Environmental Bioremediation and Toxicology, 2024)
There is growing concern about the increasing levels of lead acetate in the environment, primarily due to unsafe mining and natural resource extraction. Nigella sativa oil, a natural herbal product, is used to treat many diseases. Its pharmacological constituents have demonstrated antioxidant, anti-inflammatory, antimicrobial, and antiparasitic properties. This study investigated the protective effects of Nigella sativa oil on lead acetate-induced testicular damage in adult male Wistar rats. A total of forty-two rats were divided into six groups, each consisting of seven rats. Group I was administered normal saline equivalent to the volume given to the highest dose of treated rats. Group II received 120 mg/kg of lead acetate, while Group III (positive control) received 120 mg/kg of lead acetate and 160 mg/kg of vitamin C. Groups IV, V, and VI were administered 120 mg/kg of lead acetate followed by 6 mg/kg, 4 mg/kg, and 2 mg/kg of Nigella sativa oil, respectively, via oro-gastric intubation for seven days. The lead acetate caused a significant increase (P<0.001) in the liver enzymes (AST, ALT, and ALP). Histopathology examination showed testicular tissue damage in the lead acetate group. However, there is a great improvement in the morphology of the testicular tissue in the treated groups, even at the minimal doses. The changes in the level of biomarkers and improvement in the histomorphological appearance of the testis suggested that consumption of Nigella sativa oil does have a protective effect against lead acetate-induced testicular damage.